A study using Sepia 200c given prophylactically postpartum to prevent anoestrus problems in the dairy cow - Williamson, A.V.; Mackie, W.L.; Crawford, W.J.; Rennie, B. (British Homeopathic Journal, 1991)
The results obtained from a study model using Sepia 200c in a herd of dairy cows led to an extended study. Overall reproductive performance was monitored monthly by a farm action list and the technique of palpation of the ovaries per rectum was used to determine pregnancy and cyclical status. A total of 101 cows were randomly treated with Sepia 200c on day 14 or 21 postpartum.Statistical analysis of the results was based on the differences between the untreated Control and Sepia-treated groups in periparturient disorders and pre- and post-service periods, and between the two Sepia-treated groups.In the pre-service period, a significant difference was found between the sepia-treated groups in the proportion of heifers calved, the number of assisted calvings and pre-service problems compared to Control. A difference of 9.9 total mean days to oestrus post-treatment was found between the Sepia-treated groups.During the post-service period, significant differences were found in the conception rate to first service, the percentage of cows in calf and total culled.A reduction (non significant) was found in the 21-day treatment group compared to control and 14-day treatment in the mean days calving to conception interval and the calving index. However, between the Sepia-treated groups a significant difference was found in total mean days calving to conception interval.The results of this study appear to demonstrate a difference in effect between the Sepia-treated groups and Control group. The study has been extended into a double blind placebo trial to find the effect of using a placebo and assess the use of Sepia given earlier postpartum on herd reproductive performance.